Methodological Bases Of Teaching Mathematics And Geometry In Harmony - Ikrom Eshpo‘latovich Tursunov (Genius Journals, 2023)
This article is dedicated to the methodological foundations of teaching mathematics and geometry in harmony, to clarifying the importance of using the integration of mathematics and geometry, and to finding solutions to geometric problems using mathematical concepts, and mathematical problems using geometric concepts. It provides information about the fact that geometry is a branch of mathematics, the goals of teaching mathematics and geometry together, and the importance of mathematics in solving geometric problems.
Keywords: Mathematics; Geometry; Teaching In Harmony